Predictors of Occupational Injuries among Coal Miners: A Causal Analysis - Ghosh, Apurna; Bhattacherjee, A. (Maney Publishing, 2007)
In this study, personal and impersonal factors, such as personality, job characteristic, maturity, job satisfaction, job involvement, job stress, risk taking behaviour and safety performance, were examined as predictors of coal miners' injuries in a causal framework. A structural equation model was developed to identify the significant cause–effect relationships among the factors. This was a case control study on 202 male coal miners with at least one occupational injury during a five year period and 202 male controls with no occupational injury in their career. They were matched on job. A standardised questionnaire was used to conduct the survey and administered by personal interview. The direct effects of these variables on occupational injuries revealed that personality (?=-0·33, p<0·05), maturity (?=0&middot20, p<0·05), job characteristic (ß=-0·28, p<0·05) and safety performance (ß=-0·28, p<0·05) were the significant predictors of occupational injuries. Although job commitment has no significant direct effect on injury occurrence, it has significant indirect role (-0·04, p<0·05) in causing injury through the mediating variables. Apparently it seems that the variables job stress, job satisfaction and risk taking behaviour are not significant, but they have mediating role in injury causation which is revealed by the fact that personality (-0·15, p<0·05) and job characteristic (-0·12, p<0·05) have significant indirect effect in injury causation owing to these mediating variables. This information would help implementing preventive programs in which the firm, workers and researchers have to work together in partnership. The management should be more attentive towards working environment and safety of the workers. Factors which affect the psychological traits negatively should be improved. Workers with negative traits such as emotionally instable and older workers should be employed in less hazardous jobs.